(3fXe GdeYdheGJ GdEOGQjI (B:s (3eONd GdfXe (B/s - (3SdWGf ,GHQGgje, s ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2005)
(3ebOeI aj fXe GdeYdheGJ,eaGgje hCSGSjGJ GdfXe,eaGgje hCSGSjGJ GdeYdheGJ,GdbQGQGJ GdEOGQjI hGdeYdheGJ,fXe GdeYdheGJ hGdefXeGJ,GdOhQ GdGSJQGJjLj ddeYdheGJ,CSGSjGJ GdMGSH GdBdi,JfXje GdedaGJ hbhGYO GdHjGfGJ,GdEJUGdGJ hTHcGJ GdMGSH,fXe JLgjR GdecGJH BdjG,fXe eYGdLI GdHjGfGJ,fXe GdeYdheGJ GdEOGQjI,COhGJ hhSGFd JMdjd hHfGA GdfXe,WQb HfGA hJWhjQ fXe GdeYdheGJ,fXe JOYje GdbQGQGJ,fXe GdeYdheGJ GdEOGQI GdYdjG,GdfXe GdNHjQI,Cef hQbGHI fXe GdeYdheGJ,YhGed fLGM haTd fXe GdeYdheGJ s
Keywords: (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s